CLINICAL PROGRESSION OF ONYCHOGRYPOSIS IN GERIATRIC POPULATIONS: A LONGITUDINAL OBSERVATIONAL STUDY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Onychogryposis is a progressive nail disorder in elderly patients, marked by nail thickening and curvature that reduces mobility and quality of life. This 18-month observational study of 127 geriatric patients in Uzbekistan assessed clinical features and treatment outcomes. Most patients showed bilateral involvement, frequent infections, and significant pain with mobility limitations. Combined mechanical debridement and antifungal therapy was more effective than conservative treatment. Early diagnosis and intervention are essential to prevent functional decline in older adults.